"My World Is Upside Down": Transnational Iraqi Youth and Parent Perspectives on Resettlement in the United States. Issue 4 (2nd October 2018) - Hess, Julia Meredith; Isakson, Brian; Nelson, Matthew; Goodkind, Jessica R.
ABSTRACT: The U.S. war with Iraq led to the displacement of millions of Iraqis, many of whom have resettled in the United States as refugees. We explore the challenges Iraqi families face after resettlement, with a particular focus on the agency of refugees and challenges/opportunities of familial social reproduction in a transnational context. We conducted 181 qualitative interviews with 38 Iraqis (11 youth, 27 adults) and 5 service providers. Our findings highlight the importance of exploring refugee agency and illuminate how the interplay between structure and agency in transnational contexts is a useful framework for understanding transformations around social roles.